Effectiveness Of Reminiscence Therapy And Brain Gym On Elderly’s Conitive Function - Gati, Norman Wijaya; Hermawati; Silvitasari, Ika (Gaster, 2024)
Introduction: The Elderly is the last stage of human life development, a stage that experiences many changes and risk of experiencing illness due to the aging process. The aging process experienced by the elderly causes several changes, both changes in the physical aspect and changes in the psychological aspect. One of the changes experienced by the elderly is cognitive abilities. The cognitive abilities of the elderly are needed to help them live their lives productively. Conversely, if the elderly experience cognitive impairment, it will make the elderly experience obstacles in carrying out their daily activities. Objective: To determine the effectiveness of reminiscence therapy and brain gym on the cognitive function of the elderly. Methodology: This research used an experimental design with pre and post-tests using 2 intervention groups.  Brain gym reminiscence therapy was conducted in different groups, Result: Based on the test, the p-value of 0.632 is greater than 0.05, so it can be concluded that the cognitive level of the elderly with Reminiscence therapy is not better than the elderly who receive Brain Gym therapy. Conclusion: Brain gym therapy is proven to be more effective in dealing with cognitive impairment problems in the elderly compared to reminiscence therapy